Rachael Schneider: capstone - Schneider, Rachael, artist and filmmaker (Colorado State University. Libraries, 2015)
The artist's statement: My focus is electronic art and interactive media. As a child, I grew up in the middle of nowhere. My sisters and I had to use our imagination to entertain ourselves. Through this, I became very inquisitive. I liked to experience the world with more than just sight, and I even got in trouble for handling things that say 'do not touch' (most of the time I got blamed for breaking things, but I swear it wasn't me!). Although I only had a few, I enjoyed playing video games. I liked that the player was in control of what happened, that they had the option to become someone else, make their own story, and escape themselves for a bit. It wasn't until fairly recently, that I really got into the gaming world. I was fascinated with the interactivity of games, and how you can make it personal and have the choice to control the story. I like to combine and translate these ideas to my art: let the viewer finish the story. I have worked in a wide array of materials, from pencil and paper to digital media. I also combine the two. I draw a picture, scan it, and incorporate it into a computer game, or I laser cut, tiny, intricate designs out of paper, a task that would've been painstaking and time-consuming with an exacto. I make connections between 3D and 2D, and digital and analog. The finished product is an item that can be explored, and tell a story. I have taken to a bit of costuming and prop making which can assist in storytelling by whoever is wearing it. I am also a Projection Designer at the theatre department. The projected images or videos can help complete the scenery or create effects help to immerse the viewers. I always liked the idea of interactive art, like stories that make the viewers use their imagination, because then it becomes partially theirs, and makes the experience more personal. The viewers are an important part of the art because without them, there is no one to flip the pages, push the button, or finish the story.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, description of work, images of works and videos.
Video has no audio.
Keywords: electronic art